In-course and career outcomes predicted by medical school selection procedures based on personal qualities. (2nd August 2020) - Powis, David; Munro, Don; Bore, Miles; Burstal, Ann
Abstract: This paper reports a 40-year follow-up of 57 graduates from the initial intake to an Australian medical school who were selected on the basis of either academic criteria alone or desirable personal qualities as assessed by non-cognitive tests and an interview (with a third small group satisfying both criteria). Both students and teaching staff have remained blind to the basis for selection until the present day. Analysis of their under- and post-graduate careers indicates that 'academic' entrants were more likely to complete an intercalated BMedSci degree and to become specialists, while 'personal qualities' entrants were more likely to graduate with honours, become GPs, and win higher degrees after graduation. However, gender more significantly predicted these outcomes, with female results similar to 'personal qualities' entrants and males' similar to 'academic.' The results are interpreted with reference to the aims and structure of the Newcastle medicine curriculum.